Deconstruction Of The PAI Curriculum Based On Technological Pedagogical Content Knowledge (TPACK) Towards Mainstreaming Islamic Cybernetics Education - Mawaddah (International Journal of Technology and Education Research, 2026)
Conventional Islamic Religious Education Curriculum Still based on epistemology monodisciplinary that places revelation as the only one source truth without room dialectics adequate with digital reality, so that give birth to dichotomy religious and general knowledge, fragmentation content, as well as approach pedagogical normative- doctrinal neglect to transformation method know digital native generation. Research This aim For deconstruct Islamic Education curriculum in TPACK framework towards mainstreaming education Islamic cybernetics. Types research used is studies literature with data sources in the form of books, articles journal scientific, and reports results research. Research results disclose four findings main based on the subtitles studied. First, the epistemological problem conventional Islamic Education curriculum lies in the orientation normative-doctrinal, structure dichotomous monodisciplinary, and resistance to integration technology that causes religion to be alienated from reality existential participant educate in the room cyber. Second, deconstruction paradigmatic succeed dismantle binary opposition of revelation-reason and text-context as well as foundation monodisciplinary, open road going to organization curriculum transdisciplinarity and pedagogy transformative. Third, TPACK synthesis produces design repeat PAI content becomes contextual-applicative, pedagogy become constructivist-heutagogical, and technology as ecosystem Study adaptive that allows personalization spiritual learning. Fourth, mainstreaming education Islamic cybernetics produces prototype interconnection theoanthropocentric- digital ecosystem that places God as the Center of Control Transcendent, human as a self-organized learner, and technology as extended cognition in system curriculum autopoietic. Research conclude that transformation Islamic Education curriculum towards paradigm Islamic cybernetics is inevitability For answer digital disruption without lost essence revelation. Its implementation realized through curriculum platform development cybernetics adaptive, reorganization content transdisciplinary, strengthening teacher capacity as a learning experience designer, as well as compilation framework ethics cyber based Islamic values.